Detection of illegal estrogen administration through immunohistochemical markers in the bovine prostate - Fernández, Patricia Elena (1999)
The immunodetection of diverse cell markers was evaluated in prostatic samples from bullocks, and bullocks showing epithelial hyperplasia-metaplasia, with oestrogen-induced changes, and in experimental samples from bullocks inoculated with dietylstilbestrol (DES). Antigen-retrieval procedures allowed the use of tissues that had been fixed in formalin for long periods. Three tissue markers were chosen for the study: cytokeratins 13 and 16, vimentin and desmin. Monoclonal antibody K8.12 (specific for cytokeratins 13 and 16) stained basal cells and hyperplastic-metaplastic epithelium; monoclonal antivimentin, and desmin, allowed the definition of fibromuscular changes.